"I'm Wise to the Game": How Inner-City Women Experience and Navigate Police Raids. (October 2021) - Greene, Carolyn; Urbanik, Marta-Marika; Yankey, Manzah-Kyentoh
Despite the plethora of research on inner-city policing, little is known about how women experience and make sense of involuntary police encounters. Based upon interviews with women who had their homes raided by police in Toronto's inner-city, this paper explores how these marginalized women perceive, navigate, and resist normative gender expectations in their interactions with police officers during raids. Our findings demonstrate that women believed officers treated them according to gendered stereotypes, and in response, women strategically deployed gendered presentations in an effort to resist, negotiate, and temper anticipated raid related harms. However, participants' positionality constrained their efforts.